Effectiveness of Modern Wound Dressing on the Growth of Staphylococcus Aureus Bacteria - Gito Gito; Erna Rochmawati (University of Muhammadiyah Malang, 2018)
Wounds are classified as acute and chronic. The early stage of chronic wound formation are characterized by the emergence of gram-positive and gram-negative organisms. such as Staphylococcus aureus and Escherichia coli. At a later stage, Gram-negative Pseudomonas species tend to attack the inner layers of the wound. Modern wound dressings containing antimicrobials that have been developed since the last twenty years. It is effectively to kill bacteria and fungi in the wounds and to prevent recurrent infections during wound healings. The purpose of this paper is to report the results of a review that focuses on the effect of modern wound dressing on Staphylococcus aureus bacteria. Relevant articles were searched in PubMed and google’s scholar using keywords